Corrigendum to: Evaluation of a quality improvement intervention to reduce anastomotic leak following right colectomy (EAGLE): pragmatic, batched stepped-wedge, cluster-randomized trial in 64 countries: corrigendum - Avellaneda, Nicholas; Fütterer, Carsten Dietmar; Reißfelder, Christoph; Şandra-Petrescu, Flavius Ionuţ; Herrle, Florian; Hardt, Julia; Lamm, Lena; Seyfried, Steffen (The British journal of surgery, 2024)
This is a corrigendum to: ESCP EAGLE Safe Anastomosis Collaborative and NIHR Global Health Research Unit in Surgery, Evaluation of a quality improvement intervention to reduce anastomotic leak following right colectomy (EAGLE): pragmatic, batched stepped-wedge, cluster-randomized trial in 64 countries, British Journal of Surgery, Volume 111, Issue 1, January 2024, znad370, https://doi.org/10.1093/bjs/znad370The originally published version of this manuscript has been amended to make the following corrections to the section entitled “Collaborators”.